2019
DOI: 10.1002/chem.201900350
|View full text |Cite
|
Sign up to set email alerts
|

1,2‐Dihydro‐1‐hydroxy‐2,3,1‐benzodiazaborine Bearing an Acridine Moiety as a Circular Dichroism Probe for Determination of Absolute Configuration of Mono‐Alcohols

Abstract: A new chiral probe molecule for mono‐alcohols is developed by using 1,2‐dihydro‐1‐hydroxy‐2,3,1‐benzodiazaborine (DAB) bearing an acridine moiety 1. In the presence of mono‐alcohols, DAB 1 forms borate 2 by boronic ester formation, followed by coordination of the acridine moiety to the boron atom. Borate 2 has a chiral center on the boron atom and works as a stereodynamic circular dichroism (CD) probe molecule for chiral mono‐alcohols based on the π–π interaction between the acridine moiety and the carbon–carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…4-AA was synthesized following the procedure from Shimo et al 37 For the preparation of 1-AA, the same synthetic methodology was used with slight modifications: 1-nitroacridine was separated from its 3-nitro isomer with column chromatography (eluent: toluene/ethyl acetate/triethylamine 100:5:1), and the reduction was carried out on 10% Pd/C with hydrazine hydrate as the hydrogen source.…”
Section: Methodsmentioning
confidence: 99%
“…4-AA was synthesized following the procedure from Shimo et al 37 For the preparation of 1-AA, the same synthetic methodology was used with slight modifications: 1-nitroacridine was separated from its 3-nitro isomer with column chromatography (eluent: toluene/ethyl acetate/triethylamine 100:5:1), and the reduction was carried out on 10% Pd/C with hydrazine hydrate as the hydrogen source.…”
Section: Methodsmentioning
confidence: 99%
“…Shimo et al 58 utilised the DAB moiety to develop a probe for the determination of the absolute configuration of mono-alcohols. The probe, containing a tri-coordinated boron species ( 11 B NMR: δ = 27 ppm), was obtained by mixing 2-FPBA and acridine hydrazine.…”
Section: Iminoboronate Chemistrymentioning
confidence: 99%
“…By applying mass spectrometry, they achieved a detection limit of 0.36 mg L À1 and quantitation limits of 1.17 mg L À1 with high accuracy. Shimo et al 58 utilised the DAB moiety to develop a probe for the determination of the absolute conguration of monoalcohols. The probe, containing a tri-coordinated boron species ( 11 B NMR: d ¼ 27 ppm), was obtained by mixing 2-FPBA and acridine hydrazine.…”
Section: Repurposedmentioning
confidence: 99%
“…The mechanism of the borate formation is different from that of our previous DAB system with an acridine moiety. [5] In the previous system, the acridine nitrogen directly coordinated to the boron atom upon the boronic ester formation with alcohols (Scheme 1a). In contrast, the 2-quinoline moiety of DAB 1 worked as a Brønsted base to TFA and the generated CF 3 COO À anion coordinated to the boron atom (Figure 1a).…”
mentioning
confidence: 99%
“…[3] We have focused on 1,2-dihydro-1-hydroxy-2,3,1-benzodiazaborine (DAB), a boron-containing heteroaromatic compound that is easily synthesized from 2-formylphenylboronic acid and hydrazine, [4] and recently reported a chiral probe for monoalcohols by utilizing boronic ester formation of DAB bearing an acridine moiety (Scheme 1a). [5] During further investigation into DAB-based sensing systems, we have unexpectedly found that DAB 1 with a 2-quinoline moiety was readily converted to corresponding borates 2 upon addition of carboxylic acids, which exhibited strong AIE effects (Scheme 1b).…”
mentioning
confidence: 99%